EVALUASI PENGGUNAAN APLIKASI E-COMMERCE DENGAN USER EXPERIENCE QUESTIONNAIRE - Ryansyah, Muhamad; Sidik, Sidik; Sudibyo, Aji; Sopandi, Robi (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The online shop application makes it easy for buyers to shop online without the need for time or location restrictions. In Indonesia, there are three online shop applications that are widely used by buyers, namely Shopee, Tokopedia, and Bli-bli. All three are competitors in the same market, namely online after-sales sales services. Observation results show that the number of one-star reviews for the Shopee, Tokopedia and Bli-bli applications on the Play Store is still quite large, the reviews are generally related to user experience issues. This research aims to find out the results of evaluating user experience on the Shopee, Tokopedia, and Bli-bli applications using the User Experience Questionnaire. This research has criteria for respondents, namely Shopee, Tokopedia, and Bli-bli application users who are at least 18 years old. This research shows that the results of evaluating user experience on the Shopee mobile application are the variables Attractiveness (Mean = 2.186), Perspicuity (Mean = 1.180), efficiency (Mean = 2.186), Dependability (Mean = 2.092), Stimulation (Mean = 2.085), and Novelty (Mean = 1.881). The results of evaluating user experience on the Tokopedia application are based on the UEQ variables measuring Attraction (Mean = 1.796), Sharpness (Mean = 0.981), efficiency (Mean = 1.980), Dependability (Mean = 1.783), Stimulation (Mean = 1.462), and Novelty (Mean = 1.287). And the results of evaluating the Bli-bli user experience are Attractiveness (Mean = 2.283), Intelligence (Mean = 1.189), Efficiency (Mean = 2.380), Dependability (Mean = 2.286), Stimulation (Mean = 2.294), and Novelty (Mean = 2.000).